Responsive Regulation in Telecommunications: New horizons for the Anatel’s Enforcement - Silva, João Marcelo Azevedo Marques Mello da (Law, State and Telecommunications Review, 2017)
Purpose ”“ The purpose of this article is to assess the use of responsive regulation strategies in the debate about the new Brazilian telecommunications framework. Methodology/approach/design ”“ The Responsive Regulation Theory proposed by Ayres and Braithwaite is used as lenses to evaluate Anatel’s quality management and command and control model. Findings ”“The research showed that Anatel is using, even though in an embryonic manner, responsive regulation techniques in the new regulation that will be applied in the new Brazilian telecommunications framework. Practical implications ”“ The result of this work can be used to improve the regulation by Anatel. Originality/value ”“ The research showed that Anatel tends do use responsive regulation strategy in a regular manner.